Sultan Baharuddin Harahap: Kiprahnya dalam Pengembangan Pendidikan Islam di Kabupaten Tapanuli Selatan - HTS, Wike Wijayanti; Hanum, Azizah; Arsyad, Junaidi (el Buhuth: Borneo Journal of Islamic Studies, 2024)
The purposes of this research is to obtain the biography, contributions and progress of Sultan Baharuddin Harahap in South Tapanuli. The research method used is qualitative research with a character study approach. This writing was produced by collecting data obtained by reading references through articles, journals, books, then approaching the family, loyal bodyguards of Sultan Baharuddin Harahap, friends of Sultan Baharuddin Harahap's wife, and heads/managers of educational institutions left behind by the Sultan. Baharuddin Harahap. The results of the research show that Sultan Baharuddin Harahap is a famous king in South Tapanuli Regency who has the title "Daulat Raja Tuantua Patuan Nagaga Najungal". Apart from that, he also plays a role as a religious and traditional figure, preserving the local wisdom of Dalihan Natolu and local culture which had been in suspended animation, then contributed to establishing the Baharuddin Modern Islamic Boarding School in Janji Mauli, and RA Al-Muta'allimin Bagas Godang, Donor of Pani Asuhan, established a tareqat/parsulukan place located at Tolang Jae.